ACCOUNTING PRACTICES AND SMALL BUSINESS SUSTAINABILITY: A COMPARATIVE STUDY OF INDIA AND OMAN - Modha, Nandini Ashokkumar; Damodaran, Deepa; Sharma, Bhawna (International Journal of Research -GRANTHAALAYAH, 2025)
Small businesses form the backbone of most economies, making significant contributions to employment and innovation. However, their survival often depends on effective financial management. This paper examines the crucial role of accounting in promoting small business success, concentrating on how accurate record-keeping, financial reporting, and compliance practices facilitate informed decision-making and long-term sustainability. Drawing on comparative insights from India and Oman, as well as practical observations from an internship experience, the study highlights the benefits of structured accounting systems and the challenges faced by small enterprises in adopting them. The analysis emphasizes that accounting is not merely a technical requirement but a strategic tool that enhances credibility, improves cash flow management, and enables growth. The findings suggest that greater awareness, affordable digital tools, and training can strengthen accounting practices in small businesses, ultimately contributing to their long‑term viability.